Grazing behaviour of dairy cows on biodiverse mountain pastures is more influenced by slope than cow breed. (8th May 2019) - Koczura, M.; Martin, B.; Bouchon, M.; Turille, G.; Berard, J.; Farruggia, A.; Kreuzer, M.; Coppa, M.
Abstract : The aim of this study was to determine how cows with different genetic merit behave and perform when grazing biodiverse and heterogeneous mountain pastures with different slopes. Three groups of 12 cows in late lactation, each composed of four Holstein, four Montbéliarde and four Valdostana Red Pied cows, breeds of increasing presumed robustness and decreasing milk yield (MY ) potential. Cows grazed without concentrate either on a low-diversity flat pasture or on two species-rich mountainous pastures having slopes of either 7° or 22°. Milk yield, BW and grazing behaviour were monitored two times in the first and once in the second grazing cycle. Cows of different breeds had similar behaviour on all pastures. The Montbéliarde cows performed close to their production potential; Holstein and Valdostana cows produced less milk than anticipated. No breed difference in terms of BW loss was found. The Valdostana cows exhibited the least selective behaviour with respect to plant species and plant growth stage. Still, all cows searched for the most palatable vegetation regardless of pasture diversity. On the steep pasture, cows optimised the trade-off between ingesting and saving energy to obtain feed. They remained longer at the lowest zone and selected forbs, whereas cows on the flatter pasture went to the upper zone to select grasses. The present study gave no evidence for a superior short-term adaptation to harsh grazing conditions through an optimised feeding behaviour of the Valdostana breed compared to Montbéliarde and Holstein cows.